LEISURE ANDP ARTICIPATION IN PUBLIC POLICIES FOR YOUNG PEOPLE OF THE STATE OF ACRE/BRAZIL (Fiep Bulletin - online, 2013)
In Brazil, in the last decade, the youthsgainedagoodposition in thesocial and political agenda.Local and national youth organizations, governmentaland non-governmental andUnitedNationsagainguidedattentionandinitiativesaimedatyouths.This studyaimedtoidentifypublicpoliciesleisureandcivic and political participationpracticedin the state ofAcre/Braziland the type ofmanagementpoliciesfortheseyouth.We performed abibliographicanddocumentary research, interviews withmanagersandyoungpeopleof the city ofRioBranco.WefoundthatleisurewasnotanidentitywithintheFederal and Stategovernmentandthatprogramsaredevelopedincipientdemandfortender. The processesinherentinthemanagementof public policies foryouthandsportandleisureinAcrefollowwhathappensorisproposedby the Federal Government.There are nospecificactionsof local government.
Keywords: leisure; participation; youth